The effect of physical characteristics on cow price differentials in Kansas - Brazle, F.; Mintert, J.; Schroeder, Ted C.; Grunewald, O. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A survey of cow sales was conducted in the fall of 1986 and spring of 1987 at seven Kansas cattle auctions. Several factors significantly influenced cow prices, including health, estimated dressing percentage, lot size, breed, and time of sale. Changes in dressing percentage explained the major portion of cow price variation.
Keywords: Beef; Cattle prices; Dressing percentage